Adoption and use of smartphones among selected Filipino elderly in Quezon City - Castillon, Abby Pauline Mateo; Trinida, Mary Justine Clarise A. (Quezon City College of Home Economics, University of the Philippines Diliman, 2021)
Smartphones have cellular and computer functions that are innovative and currently provide a peculiar benefit like sending emails, video calls, searching on websites and convenience to the users. However, not all members of the society, specifically the elderly who have limited knowledge in the technology, are fully adopting and using it. In this study the initial and the regular use of the smart phone among elderly were investigated, as well as their motivations or considerations and challenges faced in using the smart phone and their level of satisfaction in the use of smart phone. This study implemented mixed methods research, using quantitative data to describe the adoption and use of smartphones of 30 purposively sampled elderly participants from Quezon City. This study showed that the elderly generally learned to use smartphones from reading the manual and sometimes asking for instructions from relatives. Their main reason for using smartphones was to communicate with their relatives living far from them. They also reported that they find the device’s keypad challenging to use when texting and the constant update in the system results in as low functioning device. Despite these challenges, the satisfaction of use among the elderly is still high, and the majority of the participants are willing to continue to use smartphones in the future. As the elderly continue to adopt smartphones, this study recommends that the smartphones should have features and applications that can help elderly in using the device. It likewise suggests that the elderly should try to explore the other features of smartphones, aside from call and messaging, and that the family members of the elderly must be aware of the experiences of their senior members in using smartphones in order to assist them when necessary.
Thesis (Bachelor of Science in Home Economics) -- University of the Philippines Diliman
Bibliography: pages 31-34.
Keywords: Technology and older people -- Philippines -- Quezon City; Older people -- Philippines -- Quezon City; Smartphones -- Philippines